1999
DOI: 10.1007/s002130050925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a selective dopamine D 1 agonist (ABT-431) on smoked cocaine self-administration in humans

Abstract: These data suggest that D1 agonists may have potential utility for the treatment of cocaine abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 29 publications
(31 reference statements)
6
75
1
Order By: Relevance
“…Choice procedures have also been used to study cocaine self-administration in humans (Haney et al, 1998(Haney et al, , 1999(Haney et al, , 2001Hart et al, 2000;Walsh et al, 2001) and to study choice maintained by other drugs of abuse, such as opiates and ethanol (Griffiths et al, 1976;de Wit and Chutuape, 1993;Heyman, 1993;Williams and Woods, 2000). The primary goal of the present study was to build on previous experience with choice procedures and identify conditions that would permit more rapid assessment of choice.…”
Section: Discussion Baseline Choice Between Cocaine and Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…Choice procedures have also been used to study cocaine self-administration in humans (Haney et al, 1998(Haney et al, , 1999(Haney et al, , 2001Hart et al, 2000;Walsh et al, 2001) and to study choice maintained by other drugs of abuse, such as opiates and ethanol (Griffiths et al, 1976;de Wit and Chutuape, 1993;Heyman, 1993;Williams and Woods, 2000). The primary goal of the present study was to build on previous experience with choice procedures and identify conditions that would permit more rapid assessment of choice.…”
Section: Discussion Baseline Choice Between Cocaine and Foodmentioning
confidence: 99%
“…Choice procedures are being used with increasing frequency to evaluate candidate pharmacotherapies in human studies (Haney et al, 1998(Haney et al, , 1999(Haney et al, , 2001Walsh et al, 2001), but to date, choice procedures have been used only sparingly for this purpose in preclinical research Balster, 1979, 1981). In the present study, the monoamine releaser damphetamine was tested as a candidate 'agonist' medication, because it produces many cocaine-like effects (Colpaert et al, 1979;Hoffman, 2001), and because several recent clinical studies reported promising results with d-amphetamine maintenance in the treatment of stimulant abuse (Fleming and Roberts, 1994;Charnaud and Griffiths, 1998;White, 2000;Grabowski et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…No effect (Haney 1999) No data No data Increase with low dose of cocaine; no effect with high dose of cocaine (Haney 2001) Subjective effects of cocaine in a laboratory setting Decrease (Haney 1999) No data Decrease (Romach 1999) Increase (Haney 2001) Craving for cocaine in a laboratory setting Decrease (trend) (Haney 1999) No data Decrease (Romach 1999) Decrease (with placebo cocaine) (Haney 2001) …”
Section: Alcoholmentioning
confidence: 99%
“…However, as shown in Table 3, cross-species comparison is impeded by differing administration schedules. For example, ABT-431 blocks reinstatement more effectively after chronic administration (Self et al 2000), but the one published human laboratory study used acute administration only, leaving open the possibility that chronic administration would be more effective (Haney et al 1999). Conversely, for ecopipam, human chronic-administration data are available (Haney 2001), but there are no chronic-administration reinstatement data with which they can be compared.…”
mentioning
confidence: 99%
“…In addition, pretreatment with D 1 and D 2 agonists produces opposite effects on cocaine's ability to reinstate this behavior, since D 1 agonists attenuate and D 2 agonists facilitate cocaine seeking induced by cocaine priming injections (Self et al, 1996;Alleweireldt et al, 2003). A similar D 1 /D 2 dichotomy regulates cocaine seeking in non-human primates (Khroyan et al, 2000), and also may suppress and stimulate craving responses in humans, respectively (Haney et al, 1998(Haney et al, , 1999. Together, these studies suggest that D 2 receptors could play a major role in eliciting relapse to cocaine seeking when environmental stimuli such as cocaine-related cues or stress activate the mesolimbic dopamine system (Phillips et al, 2003;Pruessner et al, 2004), while D 1 receptor tone may provide inhibitory regulation over cocaine seeking.…”
Section: Introductionmentioning
confidence: 99%